The primacy of politics: Towards a more realistic liberalism. Issue 4 (March 2015) - Sleat, Matt
<x xml:space="preserve">Abstract</x> Matt Sleat asks how liberal politics can recharge its vision and ideals for a contemporary reality marked by increased political disengagement and the rise of populism. The answer, he argues, lies in a dialled‐down sense of morality, a willingness to compromise, and an unerring eye on power in all its forms.